Continuous hydrogen production from glucose/xylose by an anaerobic sequential batch reactor to maximize the energy recovery efficiency. Issue 37 (6th June 2018) - Zhao, Lei; Guo, Wan-Qian; Guo, Xu-Chao; Ren, Hong-Yu; Wu, Jie-Ting; Cao, Guang-Li; Wang, Ai-Jie; Ren, Nan-Qi
Abstract : Fermentation of both glucose and xylose is essential to realize efficient bioconversion of renewable and abundant lignocellulosic biomass to hydrogen. Abstract : Fermentation of both glucose and xylose is essential to realize efficient bioconversion of renewable and abundant lignocellulosic biomass to hydrogen. In this study, a mixture of glucose and xylose at different ratios was used as a substrate for biological hydrogen production by an anaerobic sequential batch reactor (ASBR). An average glucose and xylose consumption of 80% and 50% with a high hydrogen production rate of 7.1 ± 0.9 mmol L −1 h −1 was obtained, respectively. Hydraulic retention time (HRT) played a critical role in hydrogen production at high glucose to xylose ratios. A maximum hydrogen production rate of 8.9 mmol L −1 h −1 was achieved at an optimized HRT of 12 h with a high glucose and xylose consumption of 92.2% and 82.2%, respectively. Upon further energy conversion analysis, continuous hydrogen production by ASBR provided the maximum energy conversion efficiency of 21.5%. These results indicate that ASBR can effectively accelerate the hydrogen production rate, improve substrate consumption regardless of the glucose to xylose ratio, and thus provides a new direction for efficient hydrogen production from lignocellulosic feedstock.